Association between Oral Potentially Malignant Disorders and ABO Blood Groups - S.R. , Ashwinirani; Suragimath, Girish; Doshi, Divyanee (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The World Health Organization (WHO) defined the term "potentially malignant disorders" (PMD) as the risk of malignancy being present in a lesion or condition either during the time of initial diagnosis or at a future date. Clinically, PMD appears as a white or red patch with or without symptoms. The aim of the present study was to analyze the association between ABO blood groups and oral PMD.Materials and methods: Hundred patients with clinically diagnosed PMD were included in the study. Patients who were not willing to give their blood sample for estimations of blood group were excluded from the study. ABO blood grouping was carried out using an Eryscreen Plus Kit.Statistical analysis: The data collected was entered in an Excel sheet, and descriptive statistics (frequency and percentage) were calculated using SPSS software version 21.0.Results: Out of 100 PMD patients, 65% were males and 35% were females. The majority of patients were in the age group of 30-39 (30 %). The majority of lesions were oral submucous fibrosis, accounting for 48%, followed by lichen planus (27%), leukoplakia (22%), erythroplakia (2%), and discoid lupus erythematosa (1%). Association of ABO blood groups with PMD showed a majority of lesions in blood group B (38%), followed by group A (33%), group O (19%), and group AB (10%).Conclusion: Blood group B patients were more prone to developing PMD in our study. Blood group screening in patients with a history of tobacco and alcohol consumption helps in early detection of PMD and prevention of malignancies.